Electrophysiological actions of somatostatin on the atrioventricular junction in sinus rhythm and reentry tachycardia. Issue 3 (September 1986) - Webb, S C; Krikler, D M; Hendry, W G; Adrian, T E; Bloom, S R
Abstract : Because somatostatin, a neuroregulatory peptide, is found in abundance in the atria and atrioventricular node, its electrophysiological and antiarrhythmic properties were compared with those of verapamil in ten patients with paroxysmal atrioventricular tachycardia. During sinus rhythm, intravenous somatostatin slowed the heart rate whereas verapamil increased it. Though both agents prolonged atrioventricular conduction time and refractoriness, verapamil was more potent. They were equally effective at terminating reentry atrioventricular tachycardia, restoring sinus rhythm in six of seven patients. Whereas verapamil consistently blocked conduction in the atrioventricular node, somatostatin usually induced ventricular extrasystoles at the time of conversion. Somatostatin may have physiological importance in the neurohumoral control of cardiac impulse formation and conduction.